Dynamics of Population, Agricultural Land, and Vegetated Areas in the Central to Eastern Mountain and Hill Districts of Nepal - Chidi, Chhabi Lal; Shrestha, Uttam Sagar; Sharma, Puspa; Shrestha, Prajwal; Shrestha, Sujata (The Third Pole: Journal of Geography Education, 2024)
Depopulation and agricultural land abandonment are the common occurrences in rural mountainous regions worldwide. In Nepal increased wilderness is evident due to the conversion of cultivated land into forest, shrubs, and grassland. This study focuses on the central and eastern mountainous and Hill districts; where most districts have experienced negative population growth in the past two decades. Land use/ land cover maps were obtained from Lands at 8 image classification while population was collected from the National Statistical Office of Nepal. The Digital Elevation Model (DEM) was downloaded from the Shuttle Radar Topography Mission (SRTM) and topographic maps were also collected from the Survey Department of Nepal. A reality check Approach was adopted for ground verification. Maps of population, land use/ land cover, cultivated land, vegetated area, elevation, slope gradient, and slope aspect were developed. Based on these maps, changes in the spatial distribution of population, land use/ land cover, cultivated land, and vegetated area were identified and calculated. This study has revealed a significant decrease in population in higher altitudes and hill slope areas. This has resulted in large parts of cultivated lands being abandoned in this region and most excessive abandonment with the most extensive abandonment occurring in areas with marginal slop land. These lands are now converting into forests, shrubs, and grassland. It is concluded that agricultural land abandonment in the study area should not be considered solely based on physical marginality and accessibility but rather through a holistic approach that accounts for complex variability in these factors.